2001
DOI: 10.1097/00125817-200101000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Communication issues in 22q11.2 deletion syndrome: Children at risk

Abstract: Purpose: The purpose of this investigation is to describe the communication profile of children with the 22q11.2 deletion syndrome from infancy through school age and to examine the influence of other medical aspects, such as palate anomalies, learning disorders, and cardiac defects of the syndrome to communication. Methods:Seventy-nine children were examined using standardized tests of speech and language and perceptual measures of resonance and voice. Results: Results show significant delay in emergence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
85
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(103 citation statements)
references
References 23 publications
15
85
1
2
Order By: Relevance
“…Many of our patients used manual signs to enhance communication. This is also reported by others [31]. In 15 of our patients, speech difficulties led to genetic testing (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Many of our patients used manual signs to enhance communication. This is also reported by others [31]. In 15 of our patients, speech difficulties led to genetic testing (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Relative to expressive language and speech production, far less is known about receptive language skills in this population. Although most data suggest that receptive language abilities are relatively stronger in individuals with VCFS (Moss et al, 1999;Persson, Lohmander, Jonsson, Oskarsdottir, & Soderpalm, 2003;Scherer et al, 1999;Solot et al, 2001), at least one study found that expressive language skills are better developed than receptive skills (Glaser et al, 2002).…”
Section: Receptive Languagementioning
confidence: 99%
“…Given that receptive language emerges before expressive language, some [Simon et al, 2007] have suggested that the language system is slow maturing due to the more general cognitive delays. For example, Solot et al [2001] investigated language development in two groups of youth with VCFS: preschool and school-aged children. In the preschool sample, receptive language was an area of relative strength; in the school-aged sample, the opposite pattern was evident.…”
Section: Cognitive Relative Strengthsmentioning
confidence: 99%